Metemoglobinemia e nitrato nas águas Methemoglobin and nitrate levels in drinking water - Nilda Gallego Gándara de Fernícola; Fausto Antonio de Azevedo (Universidade de São Paulo, 1981)
Foram determinados os níveis de metemoglobina em 116 crianças (idade média de 15 meses) do Estado de São Paulo (Brasil). Dois grupos foram formados: Grupo 1, por 92 crianças que consumiam água com teores de nitrato inferiores ao limite de 10 mg N/litro; e Grupo 2, por 24 crianças que bebiam água de poço com níveis de nitratos superiores ao permitido. A metemoglobinemia média do Grupo 1 (0,56%) mostrou-se estatisticamente diferente e inferior (alfa = 0,05) à do Grupo 2 (0,76%). Methemoglobin levels were determined in the blood samples of 116 children (average age, 15 months) living in the State of S. Paulo (Brazil). Blood from two groups was analyzed: Group 1 was formed by 92 children who drank water with nitrate levels below 10 mg N/liter; whereas Group 2 was formed by 24 children who drank well water with nitrate above the level permitted. The methemoglobin average for Group 1 (0.56%) was statistically different and less that for Group 2 (0.76%).